MANAJEMEN PEMBINAAN DISIPLIN PESERTA DIDIK DI MADRASAH TSANAWIYAH : PENELITIAN DI MADRASAH TSANAWIYAH 01 DARUSSALAM KEPAHIANG - Aprilia , Tika Dwi; Warsah , Idi; Warlizasusi , Jumira (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
Discipline is an important aspect in all matters, as it brings positive outcomes in various areas. This study aims to analyze the management of student discipline development at Madrasah Tsanawiyah (MTs) 01 Darussalam Kepahiang. Discipline development is a crucial factor in creating a conducive learning environment that supports both academic success and character building in students. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews with the school principal, teachers, and students, as well as documentation related to discipline policies and their implementation at the madrasah. The findings indicate that the management of discipline development at MTs 01 Darussalam involves systematic planning, consistent implementation, and continuous evaluation. The strategies include establishing clear rules, enforcing educative sanctions, strengthening Islamic values, and fostering discipline through extracurricular activities. Supporting factors for successful discipline development include the principal’s leadership, teacher involvement in supervision, and active parental participation. However, challenges faced include limited supporting facilities and discrepancies in perceptions of discipline between teachers and students. This study recommends enhancing teacher training on discipline management, providing adequate facilities, and strengthening collaboration between the school and parents to achieve more effective discipline development. In doing so, the discipline programs at MTs can be further optimized to support the character development of students.